Traditional Crafts in the Bukhara Emirate in the Second Half of the 19th Century - the Beginning of the 20th Century - Ikromjon Azizov (Researchparks Publishing, 2022)
In the second half of the 19th century and the beginning of the 20th century, as a result of the introduction of industry into the Emirate of Bukhara, traditional crafts, despite some changes, retained their traditional features. As a result of industrialization, craftsmen lost some of their jobs and were forced to engage in other occupations.